Phytochemical Screening of Active Secondary Metabolites and Antibacterial Activity Kaffir Lime Leaf (Citrus hystrix) and Tumeric Leaf (Curcuma longa Linn.) Against Escherichia coli - Suryani, Novia; Munawar, Faradillah; Hajaroh, Siti (ALKIMIA, 2021)
This study aims to determine the content of active compounds of secondary metabolites and antibacterial activity of secondary metabolites from a maceration of turmeric leaf (Curcuma longa Linn.) and kaffir lime leaf (Citrus hystrix) against Escherichia coli (E. coli). Each sample of kaffir lime leaf and turmeric leaf was extracted by maceration method using 96% ethanol solvent for 3 x 24 hours and the solvent was changed every 1 x 24 hours, then the filtered filtrate was thickened using a rotary evaporator. The phytochemical screening test was carried out by qualitative method using chemical reagents. The antibacterial activity test of the extract of the combination of turmeric leaves (Curcuma longa Linn.) and kaffir lime leaves (Citrus hystrix) used the Punch Hole Diffusion method with various concentrations of 20%, 40%, 60%, 80%, and 100%. The results showed that the combined extract of turmeric leaf (Curcuma longa Linn.) and kaffir lime leaf (Citrus hystrix) contained secondary metabolites in the form of flavonoids, alkaloids, steroids, tannins, and saponins. The optimum zone of inhibition to inhibit the growth of E. coli produced was 9.73 ± 0.78 mm. Overall, it can be concluded that the combined extract of turmeric leaf (Curcuma longa Linn.) and kaffir lime leaf (Citrus hystrix) has potential as an alternative to antibacterial active compounds.